2016
DOI: 10.1007/s10578-016-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective Mental Health Screening in Adolescents: Should We Collect Data from Youth, Parents or Both?

Abstract: Youth- and parent-rated screening measures derived from the Strengths and Difficulties Questionnaire (SDQ) and Development and Well-Being Assessment (DAWBA) were compared on their psychometric properties as predictors of caseness in adolescence (mean age 14). Successful screening was judged firstly against the likelihood of having an ICD-10 psychiatric diagnosis and secondly by the ability to discriminate between community (N = 252) and clinical (N = 86) samples (sample status). Both, SDQ and DAWBA measures ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
(61 reference statements)
3
51
0
Order By: Relevance
“…According to hypothesis 4, our findings confirm results of previous studies based on clinical settings that adolescent self-report show limited value for assessing ADHD [46, 47], CD [48], and ODD [32, 49]. Although some studies have previously found higher correlations between parent and youth reports for externalizing disorders [5–7, 19] and that self-reports can discriminate youth referred for conduct disorder from normal controls [50], our findings show limited additional value resulting from including self-reports to detect externalizing mental health problems in both the community and clinical samples. In clinical settings, youth may minimize problems to gain favorable reports from their clinicians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to hypothesis 4, our findings confirm results of previous studies based on clinical settings that adolescent self-report show limited value for assessing ADHD [46, 47], CD [48], and ODD [32, 49]. Although some studies have previously found higher correlations between parent and youth reports for externalizing disorders [5–7, 19] and that self-reports can discriminate youth referred for conduct disorder from normal controls [50], our findings show limited additional value resulting from including self-reports to detect externalizing mental health problems in both the community and clinical samples. In clinical settings, youth may minimize problems to gain favorable reports from their clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…The current study adds to previous findings on the validity of multi-informant assessments of mental disorders in youth [5, 19]. Unlike earlier studies, the present investigation is based on internet-based instruments only.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, elementary school teachers may have a more intimate knowledge of typical pattern of social emotional responding for a particular child. Furthermore, students in middle and high school may be better able to recall their own psychological experiences compared to younger children who may lack the cognitive ability to do this (Dowdy & Kim, 2012; Kuhn et al, 2017). However, while older children may have the cognitive ability to report on their experiences, adolescence is a transitional life phase and there is active debate on which informant is best for reporting this age group (Kuhn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, students in middle and high school may be better able to recall their own psychological experiences compared to younger children who may lack the cognitive ability to do this (Dowdy & Kim, 2012; Kuhn et al, 2017). However, while older children may have the cognitive ability to report on their experiences, adolescence is a transitional life phase and there is active debate on which informant is best for reporting this age group (Kuhn et al, 2017). Thus, this study extends the literature by investigating the relationship between student and teacher respondents' answers within a high school setting on the SDQ and SRSS‐IE.…”
Section: Introductionmentioning
confidence: 99%